Investigating the effect on biogenic amines, nitrite, and N-nitrosamine degradation in cultured sausage ripening through inoculation of Staphylococcus xylosus and lactic acid bacteria - Hu, Panpan; Ali, Urooj; Aziz, Tariq; Wang, Li; Zhao, Jianying; Nabi, Ghulam; Sameeh, Manal Y.; Yu, Yanqin; Zhu, Yingchun (Frontiers in Microbiology, 2023)
Microbial inoculants have the capability to reinvent the value and edible security of cultured sausages. Various studies have demonstrated that starter cultures made up of Lactic acid bacteria (LAB) and Staphylococcus xylosus (known as L-S) isolated from traditional fermented foods were used in fermented sausage manufacturing. The impact of the mixed inoculation cultures on the limiting of biogenic amines, nitrite depletion, N-nitrosamine reduction, and metrics of quality was evaluated. Inoculation of sausages with the commercial starter culture (SBM-52) were also evaluated for comparison. Results showed that the L-S strains could rapidly decrease the water activity (Aw) and pH of fermented sausages. The ability of the L-S strains to delay lipid oxidation was equivalent to the SBM-52 strains. The non-protein nitrogen (NPN) contents of L-S-inoculated sausages (0.31%) were higher than that of SBM-52-inoculated sausages (0.28%). After the ripening process, the nitrite residues in the L-S sausages were 1.47 mg/kg lower than that in the SBM-52 sausages. Compared to the SBM-52 sausages, there was a 4.88 mg/kg reduction in the biogenic amines’ concentrations in L-S sausage, especially for histamine and phenylethylamine concentrations. The N-nitrosamine accumulations of the L-S sausages (3.40 ug/kg) were lower than that of the SBM-52 sausages (3.70 ug/kg), and the NDPhA accumulations of the L-S sausages were 0.64 ug/kg lower than that of the SBM-52 sausages. Due to their significant contributions to nitrite depletion, biogenic amine reduction, and N-nitrosamine depletion in fermented sausages, the L-S strains have the potential to serve as an initial inoculant in the process of manufacturing fermented sausages.